Perlindungan Hukum Terhadap Pengguna Jaringan Indihome Atas Gangguan Jaringan Di Tinjau Dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Santi Carolin Tesa Tae; Celina Tri Siwi; Diah Imaningrum (Universitas Katolik Widya Karya Malang, 2023)
According to the Association of Indonesian Internet Service Providers, internet network users in Indonesia have increased. This increase in internet network users occurred in various places such as Atambua City, East Nusa Tenggara. Based on data from PT Telkom Indonesia, the Atambua branch, there was an increase in 1000 IndiHome internet users from 2019-2020. However, the increasing number of internet network users in Indonesia, the more cases that harm consumers, so a legal protection is needed. The formulation of the problem in this study is how to practice legal protection against IndiHome internet network users for internet network disturbances at PT Telkom Indonesia Atambua Branch and how the responsibility of PT Telkom Indonesia Atambua branch in dealing with internet network disturbances experienced by IndiHome network users. The research method used by the author in this research is a type of empirical juridical research. The results of this study indicate that PT Telkom Indonesia Atambua Branch has provided legal protection to IndiHome service users through a subscription contract signed by both parties and a form of legal protection that is provided preventively and repressively. The form of responsibility given by PT Telkom Indonesia Atambua Branch adheres to the principle of absolute responsibility or strict liability. The advice that the author can give is to PT Telkom Indonesia Atambua Branch the legal protection provided must be maximized again because in the subscription contract there are several consumer or customer rights that are not listed.